Efektivitas Penggunaan ChatGPT sebagai Media Pendamping Belajar dalam Meningkatkan Kemampuan Menulis Esai Bahasa Indonesia. - Siti Aulia Rahma; Muhammad Rizky Pratama; Ahmad Fadli Kurniawan (Educational Note, 2026)
Essay writing ability is an essential competence in Indonesian language learning because it requires students to develop ideas logically, systematically, and in accordance with linguistic rules. However, limited vocabulary, difficulties in constructing arguments, and low learning motivation remain obstacles in the learning process. The development of generative artificial intelligence, particularly ChatGPT, offers a learning companion medium that can provide rapid, interactive, and personalized feedback. This study aims to analyze the effectiveness of using ChatGPT as a learning companion medium in improving Indonesian essay writing skills. The research employed a quantitative approach with a quasi-experimental design through a pretest-posttest control group design. The sample consisted of 64 senior high school students who were divided into experimental and control classes. Data were collected through essay writing ability tests using an analytic rubric covering the aspects of content, organization, language use, vocabulary, and writing mechanics, with high inter-rater reliability (ICC = 0.87). Data were analyzed using an independent samples t-test and normalized gain. The results showed that the improvement in writing ability of the experimental class was significantly higher than that of the control class, t(62) = 3.41, p = 0.001, with a large effect size (Cohen’s d = 0.86), particularly in idea development, paragraph coherence, and language accuracy. The findings indicate that ChatGPT is effective as a learning companion medium to support independent, reflective, and sustainable writing practice under teacher supervision while paying attention to academic ethics and the originality of the work